Post-apartheid South Africa: An economic success story? - Mats Lundahl; Lennart Petersson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
The paper provides an evaluation of the development of the South African economy since the end of apartheid in 1994. Taking the 1993 situation as the point of departure, it gives an account of the path leading to the formulation of the major policy documents, and examines to what extent their objectives have been met. It highlights poverty reduction and redistribution, stabilization (fiscal and monetary policy, liberalization of the capital account of the balance of payments, exchange rate policy), trade and competition policy, investment strategies and labor market policy.
Keywords: O1; O2; O5; 330; South Africa; economic development; economic policy; Entwicklung; Wirtschaftspolitik; Südafrika